Application of Crossword Puzzle Multimedia to Improve the Science Education Learning Process and Outcomes at Junior High Schools - Marlina, Reni; Oktavianty, Erwina; Silitonga, Haratua Tiur Maria; Sandra, Novi Maulidia (Jurnal Pendidikan Indonesia, 2021)
This study aims to improve the teaching and learning process and outcomes, improve the implementation process of instruction, and improve student learning outcomes by combining cooperative learning models with natural science educational crossword puzzle multimedia on the digestive system instructional material. The form of research used is Lesson study, which is designed in 2 cycles, each cycle having 1 meeting. At each meeting, students learnt in groups using the natural science educational crossword puzzle multimedia. The results showed that the application of educational crossword puzzle multimedia was carried out well in each cycle (100%) with very strong criteria. Study results also described that the average activeness of students was 100% with very strong criteria. Based on the analysis of student achievement in the cycle I with an average score of 80.29, mastery of 82.61%, and in the second Cycle 83.48 with mastery of 91.30%, it can be concluded that thr application of natural science educational crossword puzzle multimedia supports the learning process for the better and improves student learning outcomes, especially in the material of digestive system.